SISTEM DAN MANAJEMEN SKRIPSI PROGRAM STUDI TEKNIK GEOLOGI UPN “VETERAN” YOGYAKARTA BERBASIS WEBSITE - Muchamad Ocky Bayu Nugroho; Basuki Rahmad (Jurusan Teknik Informatika, 2020)
The thesis is one step that required to be passed by geological students to get a bachelor's degree. The thesis input process was manual since early study program formed in 1958 although has been changed in administration things. There are a lot of problems in administration process due to universities regulation that impacted lecturers and students. The impacts for lecturer are student's supervisor not evenly well distributed, not well connected between the specialization of lecturers and the student's thesis’s topic and still difficult to monitoring student's thesis progress. at the same time, the impact for students is difficult to meet the coordinator. Actually the main problem derived from management administration that not well organized. Management system based on the website is a solution to solve that problem using several function such as limitation for thesis supervisor, monitoring student’s progess and choosing any topic with any lecturer’s competencies independently. The step of this research are observation, interview, collecting support data and developing main system using Waterfall method. The result is a website that containing a thesis management system that could be accessed students, lecturers, and admin in order to simplifying and organizing thesis administration processes.